2015
DOI: 10.1016/j.bbr.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Wheel running reduces high-fat diet intake, preference and mu-opioid agonist stimulated intake

Abstract: The ranges of mechanisms by which exercise affects energy balance remain unclear. One potential mechanism may be that exercise reduces intake and preference for highly palatable, energy dense fatty foods. The current study used a rodent wheel running model to determine whether and how physical activity affects HF diet intake/preference and reward signaling. Experiment 1 examined whether wheel running affected the ability of intracerebroventricular (ICV) µ opioid receptor agonist D-Ala2, NMe-Phe4, Glyol5-enkeph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
19
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 51 publications
(70 reference statements)
4
19
0
1
Order By: Relevance
“…5I) during the 2nd exposure of Experiment 2. These results are consistent with our recent report that wheel running decreases preferences for previously formed preference to a familiar HF diet [26]. Taken together, these data indicate that the decreases in HF diet preference with exercise are not simply due to neophobia or a conditioning learning.…”
Section: Discussionsupporting
confidence: 93%
“…5I) during the 2nd exposure of Experiment 2. These results are consistent with our recent report that wheel running decreases preferences for previously formed preference to a familiar HF diet [26]. Taken together, these data indicate that the decreases in HF diet preference with exercise are not simply due to neophobia or a conditioning learning.…”
Section: Discussionsupporting
confidence: 93%
“…Wheel running immediately reduces intake of and preference for a HF diet regardless of its familiarity (23,29). Results of experiment 1 replicated our previous results that wheel running induces reduced intake of a novel HF diet (29) and demonstrated that plasma corticosterone levels were significantly increased and positively correlated with wheel-running activity during the two-diet-choice feeding regimen.…”
Section: Discussionsupporting
confidence: 86%
“…In recent years, a paradigm of wheel running with two-diet choice, chow vs. HF, available simultaneously has been established (23,36). We have used this paradigm to demonstrate that wheel running reduces intake and preference to a previously preferred HF diet (23). When the exposure to the HF diet and wheel-running opportunity occurs simultaneously, the reduced HF diet preference can be so profound that the rats avoid the HF diet and consume only the chow diet (29).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Both μ-opioid receptor 1 (OPRM1) and preproenkephalin (PENK) mRNA in the ventral striatum were increased in RUN females compared to SED females, while there was no change in expression level in males. A previous study also showed no change in nucleus accumbens OPRM1 gene expression profiles in male rats following access to voluntary running wheels and high-fat plus chow diets [46], yet females were not explored.…”
Section: Discussionmentioning
confidence: 99%